2011
DOI: 10.2298/sos1101047m
|View full text |Cite
|
Sign up to set email alerts
|

The effect of K2O on the crystallization of niobium germanate glasses

Abstract: The effect of K2O content on the crystallization of niobium germanate glasses with 22.7- 24.27 wt% of GeO2 and 54.59-57.48 wt% of Nb2O5 was examined. The glasses crystallize by primary crystallization and the formed crystalline phases were K6Nb6Ge4O26, K3.8Nb5Ge3O20.4 and KNbO3. Increasing the K2O content caused a decrease in the GeO2 content of the primary phases. The effect of the K2O content on the kinetics of primary crystallization was analyzed. It was demonstrated that an increase of the K2O conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Glasses in the binary system GeO 2 –Nb 2 O 5 are not reported since homogeneous glasses cannot be obtained under laboratory conditions, but a glass‐ceramics spontaneously formed under quenching were reported in the phases diagram by E.M. Levin . Glasses samples in the ternary system GeO 2 –Nb 2 O 5 –K 2 O with different molar ratios were reported in the literature . However, the systematic synthesis and characterization of glass sample varying the niobium concentration a well as crystallization process study of this system has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glasses in the binary system GeO 2 –Nb 2 O 5 are not reported since homogeneous glasses cannot be obtained under laboratory conditions, but a glass‐ceramics spontaneously formed under quenching were reported in the phases diagram by E.M. Levin . Glasses samples in the ternary system GeO 2 –Nb 2 O 5 –K 2 O with different molar ratios were reported in the literature . However, the systematic synthesis and characterization of glass sample varying the niobium concentration a well as crystallization process study of this system has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…16 Glasses samples in the ternary system GeO 2 -Nb 2 O 5 -K 2 O with different molar ratios were reported in the literature. [17][18][19][20][21] However, the systematic synthesis and characterization of glass sample varying the niobium concentration a well as crystallization process study of this system has not been reported yet. In fact, crystallization into the glasses by annealing is one of the most effective methods concerning preparation of transparent nanocrystallized glass-ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that both the crystallization peaks of PSN glass were decreased by an increase in content of potassium ions, which may be attributed to the increase crystallization activation energy of (Na,K)NbO 3 . 17 And the crystallization temperature was chosen at 900°C for 3 h in this study and the XRD spectra of the samples are shown in Fig. 2 to check the phase transformation.…”
Section: Methodsmentioning
confidence: 99%
“…These materials are usually obtained by the powder sintering route and the crystallization of these glasses [8,9]. This method requires the knowledge of nucleation, crystallization, and crystal growth [10][11][12]. The aim of the present study is the investigation of the nucleation of germanium phosphate glass under no isothermal and isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%